2010
DOI: 10.1177/112067211002000502
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tearscope-Plus versus Slit Lamp Measurements of Inferior Tear Meniscus Height in Normal Individuals

Abstract: The LTMH could be reliably measured with slit-lamp biomicroscopy without staining, but the measurements were more repeatable with Tearscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…9 To enhance visibility of the meniscus at the slit-lamp, and therefore the repeatability of TMH measurements, the use of a Tearscope has been recommended. 20 Alternatively, in measuring the TMR with reflective meniscometry there is no need to detect the upper limit of the meniscus. 21 Reflective meniscometry was suggested to be a useful surrogate for OCT measurements of TMR.…”
Section: Discussionmentioning
confidence: 99%
“…9 To enhance visibility of the meniscus at the slit-lamp, and therefore the repeatability of TMH measurements, the use of a Tearscope has been recommended. 20 Alternatively, in measuring the TMR with reflective meniscometry there is no need to detect the upper limit of the meniscus. 21 Reflective meniscometry was suggested to be a useful surrogate for OCT measurements of TMR.…”
Section: Discussionmentioning
confidence: 99%
“…Without such a device, the meniscus can also be measured by using a slit-lamp that is capable of measuring micrometers. Although lower tear meniscus height can be reliably measured by slit-lamp biomicroscopy without staining, measurements are more repeatable with Tearscope-Plus (Keeler Ltd, Windsor, UK) 52,53…”
Section: Current Methods Of Diagnosismentioning
confidence: 99%
“…Additional methods for measuring LTMH include optical coherence tomography (OCT), fundus camera, and Tearscope ® (Keeler, Windsor, UK). Fodor et al found that there is no difference between the mean measured LTMH with Tearscope ®, slit lamp, and slit lamp with fluorescein, but the repeatability is better with the Tearscope ® device [ 28 ]. OCT is an imaging modality based on the quantity of reflected light from tissues; Wang et al stated that OCT is a multifaceted technique to measure LTMH because it provides a real-time, non-invasive, high-quality image, although the mean value can be higher than that obtained by the traditional methods and the repeatability of the measurement is unfavorable [ 29 ].…”
Section: Discussionmentioning
confidence: 99%